2004
DOI: 10.1258/095148404322772688
|View full text |Cite
|
Sign up to set email alerts
|

Predicting length of stay for Medicare patients at a teaching hospital

Abstract: This research examines how the patients' characteristics and clinical indicators affect length of stay for the top five Diagnosis-Related-Groups (DRGs) for Medicare patients at a teaching hospital in the United States. The top DRGs were selected on the basis of volume per year. Teaching hospitals in the United States devote a significant amount of their resources to research and teaching, while providing treatment for patients. The ability to predict length of stay can substantially improve a teaching hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…MaWHinney et al found urgency/emergency admissions topredict longer length of stay and higher inpatient cost for a cohort of 2,481 cardiac patients. Apart from disease severity indicies, age and gender, Omachonu et al found mortality, ethnicity, martial status, emergency admission and admission from within a hospital or from another hospital to be important predictors for inpatient length of stay [ 33 ] and can therefore be assumed to also be important predictors for inpatient costs. Emergency admissions as well as admission from other care providers are thus important variables predicting cost.…”
Section: Discussionmentioning
confidence: 99%
“…MaWHinney et al found urgency/emergency admissions topredict longer length of stay and higher inpatient cost for a cohort of 2,481 cardiac patients. Apart from disease severity indicies, age and gender, Omachonu et al found mortality, ethnicity, martial status, emergency admission and admission from within a hospital or from another hospital to be important predictors for inpatient length of stay [ 33 ] and can therefore be assumed to also be important predictors for inpatient costs. Emergency admissions as well as admission from other care providers are thus important variables predicting cost.…”
Section: Discussionmentioning
confidence: 99%
“…When the finances are tight, the large differences cry out for attention. we can see, v h in major providers and teaching hospitals are higher than others, which can be explained partially by the higher cost of labor, more complex case mix (Freitas et al, 2012) and greater obligation of medical graduate education (Omachonu et al, 2004).…”
Section: Individual Hospital Effectsmentioning
confidence: 85%
“…age, sex, marital status, habits of smoking or alcohol consumption, health status at admission (e.g. Omachonu et al , ; Chang et al , ; Walczak et al , ; Marshall et al , ; Bithell and Devlin, ; Robinson et al , ); or (iii) evaluate factors based upon information of prior diseases and socioeconomic variables to identify agents at high risk of admission to hospital or post‐acute care facilities (e.g. Simonet et al , ; Donnan et al , ; Billings et al , ; Landi et al , ; Riphahn et al , ; Prieger, ; Smith et al , ; Marcantonio et al , ; Geil et al , ; Deb and Trivedi, ).…”
Section: Introductionmentioning
confidence: 99%